Effects of peer and instructor rationales on online students' motivation and achievement. (2017) - Shin, Tae S.; Ranellucci, John; Roseth, Cary J.
Highlights: First study to examine the effects of who provides a utility value rationale. First study to examine utility value rationale in applied, online setting. In the short term, peer and instructor rationales both enhanced interest and value. But at semester's end, only peer rationales enhanced academic achievement. Neither rationale enhanced long-term change in interest or value. Abstract: Providing students with a rationale, or explanation of why learning content may be useful, can enhance motivation, but it remains unclear whether the source of the rationale moderates the effect. Accordingly, this study used a randomized experimental-control design to compare the effects of instructor and peer rationales on 59 undergraduates' motivation and achievement in an online course. Both peer and instructor rationales positively influenced students' interest in and perceived utility value of upcoming course content in the short term, but only peer rationales increased students' applied knowledge and final grades at the end of the semester. Unexpectedly, peer rationales also decreased students' relatedness to instructors. Qualitative results suggest that peer rationales may influence achievement by way of identification processes, while instructor rationales focus students' attention on content.